I don't understand something in proof of this implication:

$$\int f \mathbb{1}_A d\mu \leq \int g \mathbb{1}_A d\mu $$ for all $A \in \mathfrak{F} \Rightarrow f \leq g$ $\mu-$ almost everywhere.

Proof: Because f and g are $\mu$-integrable, $\int f \mathbb{1}_A d\mu$ and $\int g \mathbb{1}_A d\mu$ are finite for all $A \in \mathfrak{F}$. Furthermore, from claim f and g are measurable, thus $\left \{ f>g \right \}=\left \{ \omega \in \Omega | f(\omega) > g(\omega) \right \} \in \mathfrak{F}.$ We must show, that $\mu({f>g})=0.$

It holds, that

$$f\mathbb{1}_\left \{ f>g \right \} \geq g \mathbb{1}_\left \{ f > g > \right \}$$

then proof continues. But, my question is why this last step holds?


If $f(x) > g(x)$ for some $x$, then $\mathbb{1}_{\{f > g\}}(x) = 1$, so $$ f(x) \mathbb{1}_{\{f > g\}}(x) = f(x) > g(x) = g(x) \mathbb{1}_{\{f > g\}}(x). $$ If $f(x) \leq g(x)$ for some $x$, then $\mathbb{1}_{\{f > g\}}(x) = 0$, so $$ f(x) \mathbb{1}_{\{f > g\}}(x) = 0 = g(x) \mathbb{1}_{\{f > g\}}(x). $$ In either case, $f(x) \mathbb{1}_{\{f > g\}}(x) \geq g(x) \mathbb{1}_{\{f > g\}}(x)$, so $$ f \mathbb{1}_{\{f > g\}} \geq g \mathbb{1}_{\{f > g\}} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.